House age and housing prices: a viewpoint of the optimal time for land redevelopment - Wang, Wen-Kai; Tsai, I-Chun (International Journal of Strategic Property Management, 2022)
The value of a property comprises the value of both the building and the land. Numerous studies have reported a nonlinear relationship between house age and housing prices, which may result from mispricing the value of the land. The paper establishes a theoretical model to evaluate the optimal time for land redevelopment and the land value after redevelopment according to the real options. Although the depreciation effect causes the value of buildings to decrease as house age increases, properties with a lower residual building value have a higher probability of being redeveloped. Thus, the depreciation effect of building value and the inverse depreciation effect of land value contribute to the nonlinear relationship between house age and housing prices. Data from Taipei City, Taiwan, are employed for empirical analysis. The results imply that where land is scarce, housing prices are unlikely to depreciate due to ageing buildings.